An experimental study of the summer and winter thermal performance of an opaque ventilated facade in cold zone of China. (15th June 2022) - Lin, Zhenghao; Song, Yehao; Chu, Yingnan
Abstract: As a promising envelope technology for energy saving, opaque ventilated facades (OVFs) have spread to various climates and regions. Nevertheless, few reports have been published on their application in a typical continental climate zone with hot summers and cold winters, especially in China. Within the framework of a Chinese nationally funded project, comparative experiments were conducted on two full-scale test rigs to assess the thermal and energy performance of an OVF in cold zone of China. By comparing the conductive heat flux across the internal wall, the facade design features, including joint opening ratio, external cladding color, air vents openness and cavity width, showed substantial impacts on the thermal behaviors of the OVFs. It was highlighted that the surface solar radiation control features most affected the summer performance, while those restricting the cavity ventilation dominated winter. By integrating the optimal solutions for each design feature, the summer- and winter-optimal OVF configurations were proposed, bringing 11.4% and 6.5% energy use reductions compared to a conventional monolithic facade, respectively. Moreover, the daytime energy-saving effects of the OVFs were proved more significant, meaning that they were more suitable for daytime use buildings. However, considering the highly differed structures for these optimal OVFs, an integrated configuration was further qualitatively proposed through a normalized analysis of all tested facades, aiming for the optimal annual performance with minimal construction and operation complexities. These results provide general guidelines for designing performance-optimized OVFs while demonstrating a climatically representative sample from cold zone of China. Highlights: Summer and winter experimental analysis of an Opaque Ventilated Facade in continental climate. Thermal influences of joint opening ratio, external color, cavity width and air vents openness. Energy savings achievable by summer- and winter-optimal OVFs compared to a monolithic facade. OVFs present better energy performance in daytime use buildings. An integrated OVF configuration adapting to hot summer and cold winter synchronously.